2017
DOI: 10.1021/jacs.6b10435
|View full text |Cite
|
Sign up to set email alerts
|

Ag–Sn Bimetallic Catalyst with a Core–Shell Structure for CO2 Reduction

Abstract: Converting greenhouse gas carbon dioxide (CO) to value-added chemicals is an appealing approach to tackle CO emission challenges. The chemical transformation of CO requires suitable catalysts that can lower the activation energy barrier, thus minimizing the energy penalty associated with the CO reduction reaction. First-row transition metals are potential candidates as catalysts for electrochemical CO reduction; however, their high oxygen affinity makes them easy to be oxidized, which could, in turn, strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
345
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(353 citation statements)
references
References 38 publications
6
345
2
Order By: Relevance
“…With respect to the alloy catalysts,itwas found that their HCOOH and CO FEs were highly dependent on the surface configurations at the respective cathodic peak potentials,w here CO 2 electroreduction reaction rates were maximum (Supporting Information, Figure S5). [27] In comparison, the catalyst PdSn/C delivered the HCOOH FE over 99 %a tt he lower potential of À0.43 V(vs.RHE). [25,26] With increasing Sn content, the HCOOH FE increases to 54 %over Pd 3 Sn/C and further up to 63 %o ver Pd 2 Sn/C.S urprisingly,t he highest FE of > 99 %for producing HCOOH was obtained over the PdSn/C catalyst at the lowest overpotential of À0.26 V. We note that negligible H 2 (FE less than 0.3 %) was produced from the HER, and CO formation was completely suppressed over PdSn/C.S ubsequently,H COOH FE decreased gradually to 73 %o ver Pd 0.5 Sn/C and 42 %o ver Pd 0.25 Sn/C when further increasing the Sn content.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…With respect to the alloy catalysts,itwas found that their HCOOH and CO FEs were highly dependent on the surface configurations at the respective cathodic peak potentials,w here CO 2 electroreduction reaction rates were maximum (Supporting Information, Figure S5). [27] In comparison, the catalyst PdSn/C delivered the HCOOH FE over 99 %a tt he lower potential of À0.43 V(vs.RHE). [25,26] With increasing Sn content, the HCOOH FE increases to 54 %over Pd 3 Sn/C and further up to 63 %o ver Pd 2 Sn/C.S urprisingly,t he highest FE of > 99 %for producing HCOOH was obtained over the PdSn/C catalyst at the lowest overpotential of À0.26 V. We note that negligible H 2 (FE less than 0.3 %) was produced from the HER, and CO formation was completely suppressed over PdSn/C.S ubsequently,H COOH FE decreased gradually to 73 %o ver Pd 0.5 Sn/C and 42 %o ver Pd 0.25 Sn/C when further increasing the Sn content.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Jiao et al . investigated Ag−Sn bimetallic catalysts with a thin SnO x shell for selective HCOOH production . In their computational analysis, surface defects, such as oxygen vacancies (V O ) and embedded hydroxyl groups from proton reduction, were examined on a partially reduced Sn II O(101) surface as shown in Figure a.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…For example, for a specific multi‐step reaction (denoted by EĈ) where a rate‐limiting chemical step occurs after a one‐electron pre‐equilibrium step, n p =1 and n q =0, and the Tafel slope is 60 mV dec −1 . Electrokinetic studies for HCOO − production over SnO 2 catalysts have shown Tafel slopes close to 60 and 120 mV dec −1 . Based on the elementary steps for HCOO − production [Equations (2)–(6)], a Tafel slope of 60 mV dec −1 is interpreted as a rate‐limiting chemical proton transfer from bicarbonate after a one‐electron transfer to CO 2 .…”
Section: Electrokinetic Studiesmentioning
confidence: 99%
See 2 more Smart Citations